Estratégias didáticas usadas em videoaulas no youtube para o estudo de conteúdos matemáticos - VIANA, Luiz Felipe Ribeiro (2022)
This study presents a descriptive research with qualitative approach. It aims to analyze the strategies used by teachers / tutors in twochannel YouTube video lessons for teaching ensemble concepts. To this end, the following speciﬁc objectives were outlined: to identify the strategies used by the teachers of the site, and to verify the effectiveness of these classes based on the comments posted in the videos. From the analysis, it was observed that the resources used for teaching sets in two channels, one channel makes use of pen and paper and the other a writing software, the channels present the content in a simple and detailed way, this video lessons evidenced that the students / users use them to remember, answer, search, clarify doubts and improve their knowledge about sets, showing that the video lessons can contribute to help, instigate, encourage and the teaching and learning of sets.